A Survey of Arabic Root Extraction Algorithms - Thalji, Nisrean Jaber (Iraqi Journal of Science, 2024)
The importance of a survey of Arabic root extraction algorithms is that it can provide a comprehensive overview of the current state of the field and the various approaches used for this task. This can be helpful for academics and professionals working on Arabic natural language processing projects, since it enables them to comprehend the advantages and disadvantages of several approaches and select the one that is best suited to the task at hand. A survey can also help to pinpoint areas that require more research and can serve as a springboard for fresh studies in this area. In general, a survey can enhance the study of Arabic root extraction and improve the quality of Arabic natural language processing tools. Researchers can use this survey to compare the performance of several algorithms and select the best one for their particular application. In this survey, the majority of the root extraction algorithms for the Arabic language were studied with a focus on identifying their advantages and disadvantages, as well as their accuracy. The algorithms were classified into various approaches. The importance of root extraction in Arabic is explored, along with its uses and applications. Also, the issues that still require research and improvement in order to improve the efficiency of algorithms were highlighted. For instance, one issue that the algorithms encounter is the absence of a unified list that encompasses all roots, patterns, and affixes. Additionally, more rules are needed to regulate the process of root extraction.